Method for producing latex composition
By controlling the pH value after maturation of the latex composition and adding sulfur-based vulcanizing agent and xanthanic acid compound, the problems of insufficient mechanical properties of the impregnated molded body and delayed allergic reactions are solved, and a high-performance impregnated molded body is achieved.
Patent Information
- Application Number
- CN202180010373.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2020-02-20
- Filing Date
- 2021-02-08
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2041-02-08
AI Technical Summary
The prior art When making impregnated molded bodies, the tensile strength, tensile elongation and tear strength are insufficient and may cause a late-onset allergic reaction.
In the maturation process of the latex composition, the pH value of 9 or above 12 hours after the start of the maturation, and the sulfur-based vulcanizing agent and xanthanic acid compound were added to the preparation process to prepare a latex composition with excellent stability.
The high tensile strength, tensile elongation and tear strength of the impregnated molded body are achieved, and the occurrence of late-onset allergic reactions are avoided.
Smart Images

Figure BDA0003757483810000331
Abstract
Description
Technical Field
[0001] The present invention relates to a method for producing a latex composition, and also relates to a method for producing a latex composition having excellent stability and capable of forming a film-molded body such as an impregnated body having excellent tensile strength, tensile elongation, and tear strength, and a method for producing an impregnated body using the latex composition obtained by such a production method. Background Art
[0002] It has long been known that a latex composition containing natural rubber latex can be dip-molded to obtain film-molded products such as pacifiers, balloons, gloves, air bags, and bags that are used in contact with the human body. However, natural rubber latex contains proteins that cause immediate allergic reactions (type I) in humans, so it sometimes has problems as a dip-molded product that comes into direct contact with living mucous membranes or organs. Therefore, research is being conducted to remove proteins from natural rubber latex by purification or to use synthetic rubber latex instead of natural rubber.
[0003] For example, Patent Document 1 discloses a latex composition as a dip molding composition, which is prepared by mixing zinc oxide, sulfur and a vulcanization accelerator in a latex of synthetic polyisoprene as a synthetic rubber. However, in the technology of Patent Document 1, although it is possible to prevent the occurrence of immediate allergies (Type I) caused by proteins from natural rubber, when a dip molded body is made, due to the vulcanization accelerator contained in the dip molded body, allergic symptoms of delayed allergies (Type IV) sometimes occur when it comes into contact with the human body. Moreover, in the case of not mixing with a vulcanization accelerator that causes delayed allergy (Type IV) symptoms, the tensile strength, tensile elongation, and tear strength of the obtained dip molded body are insufficient. Therefore, it is desired to improve the tensile strength, tensile elongation, and tear strength of the dip molded body in the case of not mixing with a vulcanization accelerator that causes delayed allergy (Type IV) symptoms.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent document 1: International Publication No. 2014 / 129547. Summary of the invention
[0007] Problem that the invention aims to solve
[0008] The present invention has been completed in view of such actual conditions, and its purpose is to provide a method for producing a latex composition having excellent stability and capable of forming film-molded bodies such as impregnated bodies having excellent tensile strength, tensile elongation, and tear strength, as well as a method for producing an impregnated body using the latex composition obtained by such a production method.
[0009] Solutions for solving problems
[0010] The present inventors have conducted intensive studies to achieve the above object and have found that the above object can be achieved by setting the pH 12 hours after the start of aging to a specific range in the aging step performed after the preparation of the latex composition, thereby completing the present invention.
[0011] That is, according to the present invention, there is provided a method for producing a latex composition, comprising: a preparation step of preparing a conjugated diene polymer latex; a preparation step of adding a sulfur-based vulcanizing agent and a xanthate compound to the conjugated diene polymer latex to obtain a latex composition before aging; and an aging step of aging the prepared latex composition before aging by storing the prepared latex composition before aging at a temperature of 5 to 60° C. for 12 hours to 14 days, wherein in the aging step, the pH of the latex composition 12 hours after the start of aging is set to 9 or above.
[0012] In the method for producing a latex composition of the present invention, it is preferred that the pH of the latex composition before aging is set to 11 or higher by the preparation step.
[0013] In the method for producing a latex composition of the present invention, it is preferred that a pH adjuster is added to the latex composition being aged in the aging step.
[0014] In the method for producing a latex composition of the present invention, the pH adjuster preferably contains at least one selected from the group consisting of alkali metal hydroxides, ammonia, and organic amine compounds.
[0015] In the method for producing a latex composition of the present invention, the sulfur-based vulcanizing agent is preferably used in an amount of 0.01 to 3 parts by weight based on 100 parts by weight of the conjugated diene polymer contained in the conjugated diene polymer latex.
[0016] In the method for producing a latex composition of the present invention, the xanthogenic acid compound is preferably used in an amount of 0.01 to 10 parts by weight based on 100 parts by weight of the conjugated diene polymer contained in the conjugated diene polymer latex.
[0017] In the method for producing a latex composition of the present invention, it is preferred that a strong acid salt-based surfactant is further added to the conjugated diene polymer latex in the preparation step.
[0018] In the method for producing a latex composition of the present invention, the conjugated diene polymer latex is preferably a latex of synthetic polyisoprene, a latex of a styrene-isoprene-styrene block copolymer, or a latex of a natural rubber from which protein has been removed.
[0019] In the method for producing a latex composition of the present invention, the conjugated diene polymer latex is preferably a latex of a conjugated diene polymer having no carboxyl group.
[0020] Furthermore, according to the present invention, there can be provided a method for producing a dip-molded article, comprising the step of dip-molding the latex composition obtained by the above-mentioned production method.
[0021] Effects of the Invention
[0022] According to the present invention, there can be provided a method for producing a latex composition having excellent stability and capable of forming a film-molded body such as an impregnated body having excellent tensile strength, tensile elongation, and tear strength, as well as a method for producing an impregnated body using the latex composition obtained by such a production method. DETAILED DESCRIPTION
[0023] The method for producing the latex composition of the present invention comprises:
[0024] A preparation step of preparing a conjugated diene polymer latex;
[0025] A preparation step of adding a sulfur-based vulcanizing agent and a xanthogenic acid compound to the conjugated diene polymer latex to obtain a latex composition before aging;
[0026] The aging step comprises: preparing the pre-aging latex composition, and then aging the pre-aging latex composition by storing the prepared pre-aging latex composition at a temperature of 5 to 60° C. for 12 hours to 14 days.
[0027] In the aging step, the pH of the latex composition is set to 9 or more 12 hours after the start of aging.
[0028] The preparation step of the present invention is a step of preparing a conjugated diene polymer latex for use in the preparation step described below. The conjugated diene polymer latex used in the present invention is not particularly limited as long as it is a latex in which a conjugated diene polymer is dispersed in water.
[0029] <Conjugated diene polymer latex>
[0030] The conjugated diene polymer latex used in the present invention is not particularly limited, and examples thereof include latex of synthetic polyisoprene, latex of styrene-isoprene-styrene block copolymer (SIS), latex of natural rubber from which protein has been removed (deproteinized natural rubber), latex of nitrile-containing conjugated diene copolymer, etc. Among these, latex of polymers containing isoprene units such as latex of synthetic polyisoprene, latex of SIS, and latex of deproteinized natural rubber are preferred, and latex of synthetic polyisoprene is particularly preferred. In addition, the conjugated diene polymer latex used in the present invention may also be a conjugated diene polymer latex having a modified group such as a carboxyl group, but based on the viewpoint of being able to reduce the number of manufacturing steps, a conjugated diene polymer latex without a carboxyl group is preferred. In addition, the conjugated diene polymer having no carboxyl group may be a conjugated diene polymer having substantially no carboxyl group, and may contain a carboxyl group in an amount caused by impurities (for example, an amount of less than about 0.05% by weight in terms of monomer units).
[0031] When a latex of synthetic polyisoprene is used as the conjugated diene polymer latex, the synthetic polyisoprene contained in the latex of synthetic polyisoprene may be a homopolymer of isoprene or a copolymer of isoprene and other ethylenically unsaturated monomers copolymerizable with isoprene. From the viewpoint of easily obtaining a film-molded product such as an impregnated product that is soft and has excellent tensile strength, the content of the isoprene unit in the synthetic polyisoprene is preferably 70% by weight or more, more preferably 90% by weight or more, further preferably 95% by weight or more, and particularly preferably 100% by weight (homopolymer of isoprene) relative to all monomer units.
[0032] Examples of other ethylenically unsaturated monomers copolymerizable with isoprene include conjugated diene monomers other than isoprene such as butadiene, chloroprene, and 1,3-pentadiene; ethylenically unsaturated nitrile monomers such as acrylonitrile, methacrylonitrile, fumaronitrile, and α-chloroacrylonitrile; vinyl aromatic monomers such as styrene and alkylstyrene; ethylenically unsaturated carboxylic acid ester monomers such as methyl (meth)acrylate (referring to "methyl acrylate and / or methyl methacrylate", and the same also applies to ethyl (meth)acrylate, etc. hereinafter), ethyl (meth)acrylate, butyl (meth)acrylate, and 2-ethylhexyl (meth)acrylate, etc. These other ethylenically unsaturated monomers copolymerizable with isoprene may be used alone or in combination of two or more.
[0033] Synthetic polyisoprene can be obtained by a conventionally known method, for example, by solution polymerization of isoprene and other copolymerizable ethylenically unsaturated monomers used as required in an inert polymerization solvent using a Ziegler polymerization catalyst composed of trialkylaluminum-titanium tetrachloride or an alkyllithium polymerization catalyst such as n-butyllithium or sec-butyllithium. The polymer solution of synthetic polyisoprene obtained by solution polymerization can be directly used to produce synthetic polyisoprene latex, but the solid synthetic polyisoprene can also be taken out from the polymer solution and dissolved in an organic solvent to produce synthetic polyisoprene latex.
[0034] In the case of obtaining a polymer solution of synthetic polyisoprene by the above method, impurities such as residues of the polymerization catalyst remaining in the polymer solution can be removed. In addition, an anti-aging agent described later can also be added to the solution during or after polymerization. In addition, commercially available solid synthetic polyisoprene can also be used.
[0035] The isoprene units in the synthetic polyisoprene include four types, namely, cis-bonding units, trans-bonding units, 1,2-vinyl-bonding units, and 3,4-vinyl-bonding units, depending on the bonding form of the isoprene. From the viewpoint of improving the tensile strength of the obtained film-molded product such as the impregnated molded product, the content ratio of the cis-bonding units in the isoprene units contained in the synthetic polyisoprene is preferably 70% by weight or more, more preferably 90% by weight or more, and even more preferably 95% by weight or more, relative to the total isoprene units.
[0036] The weight average molecular weight of the synthetic polyisoprene is preferably 10,000 to 5,000,000, more preferably 500,000 to 5,000,000, and even more preferably 800,000 to 3,000,000, based on standard polystyrene conversion by gel permeation chromatography analysis. When the weight average molecular weight of the synthetic polyisoprene is within the above range, the tensile strength, tensile elongation, and tear strength of a film molded body such as a dip molded body are further improved, and the synthetic polyisoprene latex also tends to be easy to produce.
[0037] In addition, the polymer Mooney viscosity (ML) of synthetic polyisoprene 1+4 , 100°C) is preferably 50 to 80, more preferably 60 to 80, further preferably 70 to 80.
[0038] Examples of methods for obtaining synthetic polyisoprene latex include: (1) a method of emulsifying a solution or fine suspension of synthetic polyisoprene dissolved or finely dispersed in an organic solvent in water in the presence of an emulsifier, and removing the organic solvent as needed to produce synthetic polyisoprene latex; and (2) a method of directly producing synthetic polyisoprene latex by emulsion polymerization or suspension polymerization of isoprene alone or a mixture of isoprene and an ethylenically unsaturated monomer copolymerizable therewith in the presence of an emulsifier. The production method (1) is preferred because synthetic polyisoprene having a high ratio of cis-bonded units in the isoprene units can be used and film-molded products such as dip-molded products having excellent mechanical properties such as tensile strength can be easily obtained.
[0039] Examples of the organic solvent used in the production method (1) include aromatic hydrocarbon solvents such as benzene, toluene, and xylene; alicyclic hydrocarbon solvents such as cyclopentane, cyclopentene, cyclohexane, and cyclohexene; aliphatic hydrocarbon solvents such as pentane, hexane, and heptane; and halogenated hydrocarbon solvents such as dichloromethane, chloroform, and dichloroethane. Among these, alicyclic hydrocarbon solvents and aliphatic hydrocarbon solvents are preferred, pentane, cyclohexane, and n-hexane are more preferred, and n-hexane is particularly preferred.
[0040] The amount of the organic solvent used is preferably 2000 parts by weight or less, more preferably 20 to 1500 parts by weight, and even more preferably 500 to 1500 parts by weight, based on 100 parts by weight of the synthetic polyisoprene.
[0041] As the emulsifier used in the production method of (1) above, an ionic emulsifier is preferably used, and an anionic emulsifier is more preferably used. Examples of the anionic emulsifier include fatty acid salts such as sodium laurate, potassium myristate, sodium palmitate, potassium oleate, sodium linolenate, sodium rosinate, and potassium rosinate; alkylbenzenesulfonates such as sodium dodecylbenzenesulfonate, potassium dodecylbenzenesulfonate, sodium decylbenzenesulfonate, potassium decylbenzenesulfonate, sodium hexadecylbenzenesulfonate, and potassium hexadecylbenzenesulfonate; alkylsulfosuccinates such as sodium di(2-ethylhexyl)sulfosuccinate, potassium di(2-ethylhexyl)sulfosuccinate, and sodium dioctylsulfosuccinate; alkylsulfuric acid ester salts such as sodium lauryl sulfate and potassium lauryl sulfate; polyoxyethylene alkyl ether sulfate ester salts such as sodium polyoxyethylene lauryl ether sulfate and potassium polyoxyethylene lauryl ether sulfate; monoalkylphosphate ester salts such as sodium lauryl phosphate and potassium lauryl phosphate, and the like.
[0042] Among these anionic emulsifiers, fatty acid salts, alkylbenzenesulfonates, alkylsulfosuccinates, alkyl sulfate ester salts and polyoxyethylene alkyl ether sulfate ester salts are preferred, and fatty acid salts and alkylbenzenesulfonates are particularly preferred.
[0043] In addition, from the viewpoint of being able to more efficiently remove trace amounts of residual polymerization catalysts (particularly aluminum and titanium) from synthetic polyisoprene and suppressing the generation of coagulation products when preparing the latex composition, at least one selected from alkylbenzene sulfonates, alkyl sulfosuccinates, alkyl sulfate ester salts, and polyoxyethylene alkyl ether sulfate ester salts and fatty acid salts can be used in combination. Here, as the fatty acid salt, sodium rosinate and potassium rosinate are preferred, and as the alkylbenzene sulfonate, sodium dodecylbenzene sulfonate and potassium dodecylbenzene sulfonate are preferred. In addition, these emulsifiers may be used alone or in combination of two or more.
[0044] In addition, as described above, by using at least one selected from alkylbenzene sulfonates, alkyl sulfosuccinates, alkyl sulfate esters and polyoxyethylene alkyl ether sulfate esters and fatty acid salts in combination, the obtained latex will become a latex containing at least one selected from alkylbenzene sulfonates, alkyl sulfosuccinates, alkyl sulfate esters and polyoxyethylene alkyl ether sulfate esters and fatty acid salts.
[0045] Examples of the ionic emulsifier other than the anionic emulsifier include copolymerizable emulsifiers such as sulfoesters of α,β-unsaturated carboxylic acids, sulfates of α,β-unsaturated carboxylic acids, and sulfoalkyl aryl ethers.
[0046] Furthermore, a nonionic emulsifier such as polyoxyethylene alkyl ether, polyoxyethylene alkylphenol ether, polyoxyethylene alkyl ester, polyoxyethylene sorbitan alkyl ester may be used in combination as long as the coagulation by the coagulant used in the dip molding is not inhibited.
[0047] The amount of the emulsifier used in the manufacturing method of the above (1) is preferably 0.1 to 50 parts by weight, more preferably 0.5 to 30 parts by weight, and further preferably 5 to 15 parts by weight relative to 100 parts by weight of the synthetic polyisoprene. In addition, when two or more emulsifiers are used, it is preferred that their total amount be within the above range. That is, for example, when at least one selected from alkylbenzene sulfonate, alkyl sulfosuccinate, alkyl sulfate ester salt, and polyoxyethylene alkyl ether sulfate ester salt and a fatty acid salt are used in combination, it is preferred that their total amount be within the above range. By making the amount of the emulsifier used within the above range, the generation of agglomerates during emulsification can be further suppressed.
[0048] When at least one selected from alkylbenzenesulfonate, alkylsulfosuccinate, alkylsulfuric acid ester salt and polyoxyethylene alkyl ether sulfate ester salt and fatty acid salt are used together as anionic emulsifiers, the weight ratio of "fatty acid salt" : "the total weight of at least one emulsifier selected from alkylbenzenesulfonate, alkylsulfosuccinate, alkylsulfuric acid ester salt and polyoxyethylene alkyl ether sulfate ester salt" is preferably in the range of 1:1 to 10:1, and more preferably in the range of 1:1 to 7:1. When the weight ratio of at least one emulsifier selected from alkylbenzenesulfonate, alkylsulfosuccinate, alkylsulfuric acid ester salt and polyoxyethylene alkyl ether sulfate ester salt is within the above range, foaming generated during the treatment of synthetic polyisoprene can be suppressed, thereby eliminating the need for long-term standing and adding defoaming agents, which contributes to improved workability and cost reduction.
[0049] The amount of water used in the production method (1) is preferably 10 to 1000 parts by weight, more preferably 30 to 500 parts by weight, and most preferably 50 to 100 parts by weight relative to 100 parts by weight of the organic solvent solution of the synthetic polyisoprene. The types of water used include hard water, soft water, ion-exchanged water, distilled water, zeolite water, etc., and soft water, ion-exchanged water, and distilled water are preferred.
[0050] The device for emulsifying the solution or fine suspension of synthetic polyisoprene dissolved or finely dispersed in an organic solvent in water in the presence of an emulsifier can be used without particular limitation as long as it is a commonly available commercial emulsifier or disperser. The method of adding the emulsifier to the solution or fine suspension of synthetic polyisoprene is not particularly limited, and the emulsifier may be added in advance to water or to the solution or fine suspension of synthetic polyisoprene, or to both, or may be added to the emulsion during the emulsification operation, and may be added all at once or in batches.
[0051] Examples of the emulsifying device include batch emulsifiers such as "Homogenizer" (manufactured by Aika Co., Ltd.), "Polytron" (manufactured by Kinematica Co., Ltd.), and "TK AUTO Homomixer" (manufactured by Tokushiki Kagaku Kogyo Co., Ltd.); "TK PIPELINE Homomixer" (manufactured by Tokushiki Kagaku Kogyo Co., Ltd.), "Colloid Mill" (manufactured by Kobelco Pantec Co., Ltd.), "Thrasher" (manufactured by Nippon Cokes Industries Co., Ltd.), "Trigonal Wet Micro-Pulverizer" (manufactured by Mitsui Miike Chemical Industry Co., Ltd.), "Cavitron" (manufactured by Eurotec Co., Ltd.), "Milder" (manufactured by Pacific Machinery Co., Ltd.), and "Fine Flow" (manufactured by Fujikawa Chemical Industry Co., Ltd.). Mill" (manufactured by Pacific Machinery Co., Ltd.); high-pressure emulsifiers such as the product name "Microfluidizer" (manufactured by Minoga Industry Co., Ltd.), the product name "Nanomizer" (manufactured by NANOMIZER Co., Ltd.), and the product name "APVGaulin" (manufactured by Gaulin Co., Ltd.); membrane emulsifiers such as the product name "Membrane Emulsifier" (manufactured by Renka Industry Co., Ltd.); vibration emulsifiers such as the product name "Vibration Mixer (VIBROMIXER)" (manufactured by Renka Industry Co., Ltd.); ultrasonic emulsifiers such as the product name "Ultrasonic Homogenizer" (manufactured by Branson Co., Ltd.). In addition, the conditions for the emulsification operation performed by the emulsification device are not particularly limited, and the processing temperature, processing time, etc. can be appropriately selected to achieve the desired dispersion state.
[0052] In the production method (1) above, it is desirable to remove the organic solvent from the emulsion obtained through the emulsification operation.
[0053] As a method for removing the organic solvent from the emulsion, a method is preferably used that can reduce the content of the organic solvent (preferably an alicyclic hydrocarbon solvent or an aliphatic hydrocarbon solvent) in the obtained synthetic polyisoprene latex to 500 ppm by weight or less. For example, reduced pressure distillation, atmospheric pressure distillation, steam distillation, centrifugal separation and the like can be used.
[0054] The organic solvent may be removed while adding a defoaming agent. By adding a defoaming agent, the foaming of the synthetic polyisoprene can be suppressed.
[0055] Furthermore, in order to increase the solid content concentration of the synthetic polyisoprene latex, after removing the organic solvent, a concentration operation may be carried out by using a method such as reduced pressure distillation, atmospheric pressure distillation, centrifugal separation, membrane concentration, etc. as needed. Centrifugal separation is particularly preferred from the viewpoint of being able to increase the solid content concentration of the synthetic polyisoprene latex and simultaneously reduce the residual amount of the emulsifier in the synthetic polyisoprene latex.
[0056] Centrifugal separation is preferably carried out under the following conditions, for example: a continuous centrifuge is used, the centrifugal force is preferably 100 to 10,000 G, the solid content concentration of the synthetic polyisoprene latex before centrifugal separation is preferably 2 to 15% by weight, the flow rate into the centrifuge is preferably 500 to 1,700 kg / hr, and the back pressure (gauge pressure) of the centrifuge is preferably 0.03 to 1.6 MPa, and the synthetic polyisoprene latex can be obtained as a light liquid after centrifugal separation. In addition, the residual amount of the emulsifier in the synthetic polyisoprene latex can be reduced by this.
[0057] The solid content concentration of the synthetic polyisoprene latex is preferably 30 to 70% by weight, more preferably 40 to 70% by weight, and further preferably 50 to 70% by weight. By making the solid content concentration greater than the lower limit of the above range, the film-molded body such as the dip-molded body described later is not easily damaged. In addition, by making the solid content concentration less than the upper limit of the above range, the viscosity of the synthetic polyisoprene latex can be prevented from becoming too high, and it is easy to transport in a pipeline and stir in a mixing tank.
[0058] The volume average particle size of the synthetic polyisoprene latex is preferably 0.1 to 10 μm, more preferably 0.5 to 3 μm, and even more preferably 0.5 to 2.0 μm. By setting the volume average particle size within the above range, the latex viscosity becomes moderate and easy to handle, and the formation of a film on the surface of the latex can be suppressed during storage of the synthetic polyisoprene latex.
[0059] Furthermore, the synthetic polyisoprene latex may contain additives such as a pH adjuster, a defoamer, a preservative, a crosslinking agent, a chelating agent, a deoxidizer, a dispersant, and an antioxidant, which are commonly used in the latex field.
[0060] Examples of the pH adjuster include alkali metal hydroxides such as sodium hydroxide and potassium hydroxide; alkali metal carbonates such as sodium carbonate and potassium carbonate; alkali metal bicarbonates such as sodium bicarbonate; ammonia; organic amine compounds such as trimethylamine and triethanolamine, etc., preferably alkali metal hydroxides or ammonia. The pH of the synthetic polyisoprene latex in the preparation step is not particularly limited, but as described later, when a latex composition is prepared using the synthetic polyisoprene latex and the latex composition is aged under predetermined conditions, the pH of the latex composition before aging is preferably 10 or more.
[0061] As the conjugated diene polymer latex, as described above, a latex of a styrene-isoprene-styrene block copolymer (SIS) can also be used. In SIS, "S" represents a styrene block, and "I" represents an isoprene block.
[0062] The SIS contained in the SIS latex can be obtained by a conventionally known method, for example, by block copolymerizing isoprene and styrene in an inactive polymerization solvent using an active organic metal such as n-butyl lithium as an initiator. In addition, the obtained SIS polymer solution can be directly used to manufacture SIS latex, or solid SIS can be taken out from the polymer solution and dissolved in an organic solvent to manufacture SIS latex. The method for manufacturing SIS latex is not particularly limited, but the following method is preferred: a solution or fine suspension of SIS dissolved or finely dispersed in an organic solvent is emulsified in water in the presence of an emulsifier, and the organic solvent is removed as needed to manufacture SIS latex.
[0063] At this time, impurities such as residues of the polymerization catalyst remaining in the polymer solution can be removed after synthesis. In addition, an anti-aging agent described later can also be added to the solution during or after polymerization. In addition, commercially available solid SIS can also be used.
[0064] As the organic solvent, the same organic solvent as in the case of synthesizing polyisoprene can be used, and aromatic hydrocarbon solvents and alicyclic hydrocarbon solvents are preferred, and cyclohexane and toluene are particularly preferred.
[0065] The amount of the organic solvent used is usually 50 to 2000 parts by weight, preferably 80 to 1000 parts by weight, more preferably 100 to 500 parts by weight, and further preferably 150 to 300 parts by weight, based on 100 parts by weight of SIS.
[0066] As the emulsifier, the same emulsifiers as in the case of synthesizing polyisoprene can be exemplified, and anionic emulsifiers are preferred, and potassium rosinate and sodium dodecylbenzenesulfonate are particularly preferred.
[0067] The amount of the emulsifier used is preferably 0.1 to 50 parts by weight, more preferably 0.5 to 30 parts by weight, and even more preferably 5 to 15 parts by weight relative to 100 parts by weight of SIS. When the amount of the emulsifier used is within the above range, the stability of the obtained latex can be improved.
[0068] The amount of water used in the above-mentioned method for producing SIS latex is preferably 10 to 1000 parts by weight, more preferably 30 to 500 parts by weight, and most preferably 50 to 100 parts by weight relative to 100 parts by weight of the organic solvent solution of SIS. Examples of the type of water used include hard water, soft water, ion exchange water, distilled water, zeolite water, and the like. In addition, a polar solvent represented by an alcohol such as methanol may be used in combination with water.
[0069] The apparatus for emulsifying the organic solvent solution or fine suspension of SIS in water in the presence of an emulsifier may be the same apparatus as in the case of synthesizing polyisoprene. The method for adding the emulsifier is not particularly limited, and the emulsifier may be added in advance to water or to the organic solvent solution or fine suspension of SIS, or to both, or may be added to the emulsion during the emulsification operation, and may be added all at once or in batches.
[0070] In the above-mentioned method for producing SIS latex, it is preferred to obtain SIS latex by removing the organic solvent from the emulsion obtained by the emulsification operation. The method for removing the organic solvent from the emulsion is not particularly limited, and methods such as reduced pressure distillation, atmospheric pressure distillation, steam distillation, centrifugal separation, etc. can be used.
[0071] The organic solvent may be removed while adding a defoaming agent. Adding a defoaming agent can suppress foaming.
[0072] In order to increase the solid content concentration of the SIS latex, after removing the organic solvent, a concentration operation may be carried out as necessary by using a method such as reduced pressure distillation, atmospheric pressure distillation, centrifugal separation, membrane concentration, etc.
[0073] The solid content concentration of the SIS latex is preferably 30 to 70% by weight, more preferably 40 to 70% by weight, and further preferably 50 to 70% by weight. By making the solid content concentration greater than the lower limit of the above range, a film-molded body such as an impregnated body described later is not easily damaged. In addition, by making the solid content concentration less than the upper limit of the above range, the viscosity of the SIS latex can be prevented from becoming too high, and it is easy to transport in a pipeline and to stir in a mixing tank.
[0074] In addition, the SIS latex may be formulated with additives such as a pH adjuster, a defoamer, a preservative, a crosslinking agent, a chelating agent, a scavenger, a dispersant, an anti-aging agent, etc., which are commonly formulated in the field of latex. Examples of the pH adjuster include the same pH adjusters as those in the case of synthesizing polyisoprene, preferably alkali metal hydroxides or ammonia. The pH of the SIS latex in the preparation step is not particularly limited, but as described later, when using SIS latex or the like as a latex composition and ripening the latex composition under prescribed conditions, the pH of the latex composition before ripening is preferably 10 or more.
[0075] The content of the styrene unit in the styrene block in the SIS contained in the SIS latex obtained in this manner is preferably 70 to 100% by weight, more preferably 90 to 100% by weight, and even more preferably 100% by weight based on all monomer units.
[0076] The content of the isoprene units in the isoprene block in SIS is preferably 70 to 100% by weight, more preferably 90 to 100% by weight, and even more preferably 100% by weight, based on all monomer units.
[0077] The content ratio of styrene units to isoprene units in SIS is generally in the range of 1:99 to 90:10, preferably in the range of 3:97 to 70:30, more preferably in the range of 5:95 to 50:50, and still more preferably in the range of 10:90 to 30:70, in terms of the weight ratio of "styrene units:isoprene units".
[0078] The weight average molecular weight of SIS is preferably 10,000 to 1,000,000, more preferably 50,000 to 500,000, and even more preferably 100,000 to 300,000, based on standard polystyrene conversion according to gel permeation chromatography. When the weight average molecular weight of SIS is within the above range, the balance between tensile strength and flexibility of a film-molded body such as an impregnated body is improved, and the latex of SIS tends to be easy to manufacture.
[0079] The volume average particle size of the latex particles (SIS particles) in the SIS latex is preferably 0.1 to 10 μm, more preferably 0.5 to 3 μm, and even more preferably 0.5 to 2.0 μm. When the volume average particle size of the latex particles is within the above range, the latex viscosity becomes moderately easy to handle, and the formation of a film on the latex surface can be suppressed when the SIS latex is stored.
[0080] Moreover, as the conjugated diene polymer latex, as described above, a latex of a nitrile group-containing conjugated diene copolymer can also be used.
[0081] The nitrile group-containing conjugated diene copolymer is a copolymer obtained by copolymerizing an ethylenically unsaturated nitrile monomer and a conjugated diene monomer, and may be a copolymer obtained by copolymerizing other ethylenically unsaturated monomers copolymerizable with these monomers as needed.
[0082] As conjugated diene monomers, for example, 1,3-butadiene, isoprene, 2,3-dimethyl-1,3-butadiene, 2-ethyl-1,3-butadiene, 1,3-pentadiene and chloroprene can be cited. Among these, 1,3-butadiene and isoprene are preferred, and 1,3-butadiene is more preferred. These conjugated diene monomers can be used alone or in combination of two or more. The content ratio of the conjugated diene monomer unit formed by the conjugated diene monomer in the nitrile-containing conjugated diene copolymer is preferably 56 to 78 weight %, more preferably 56 to 73 weight %, and further preferably 56 to 68 weight %. By making the content of the conjugated diene monomer unit within the above range, the tensile strength of the obtained film-molded body such as the impregnated body can be made sufficient, and the feel and elongation can be made more excellent.
[0083] As the ethylenically unsaturated nitrile monomer, there is no particular limitation as long as it is an ethylenically unsaturated monomer containing a nitrile group, and examples thereof include acrylonitrile, methacrylonitrile, fumaronitrile, α-chloroacrylonitrile, α-cyanoethylacrylonitrile, etc. Acrylonitrile and methacrylonitrile are particularly preferred, and acrylonitrile is more preferred. These ethylenically unsaturated nitrile monomers can be used alone or in combination of two or more. The content ratio of the ethylenically unsaturated nitrile monomer units formed by the ethylenically unsaturated nitrile monomers in the nitrile-containing conjugated diene copolymer is preferably 20 to 40% by weight, more preferably 25 to 40% by weight, and further preferably 30 to 40% by weight. By making the content of the ethylenically unsaturated nitrile monomer units within the above range, the tensile strength of the film-molded bodies such as the obtained impregnated bodies can be made sufficient, and the hand feel and elongation can be made more excellent.
[0084] Examples of other ethylenically unsaturated monomers copolymerizable with the conjugated diene monomer and the ethylenically unsaturated nitrile monomer include: vinyl aromatic monomers such as styrene, alkyl styrene, and vinyl naphthalene; fluoroalkyl vinyl ethers such as fluoroethyl vinyl ether; ethylenically unsaturated amide monomers such as (meth)acrylamide, N-methylol (meth)acrylamide, N,N-dimethylol (meth)acrylamide, N-methoxymethyl (meth)acrylamide, and N-propoxymethyl (meth)acrylamide; methyl (meth)acrylate, ethyl (meth)acrylate, butyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, trifluoroethyl (meth)acrylate, tetrafluoropropyl (meth)acrylate, dibutyl maleate, dibutyl fumarate, and diethyl maleate Ethylenically unsaturated carboxylic acid ester monomers such as methoxymethyl (meth)acrylate, ethoxyethyl (meth)acrylate, methoxyethoxyethyl (meth)acrylate, cyanomethyl (meth)acrylate, 2-cyanoethyl (meth)acrylate, 1-cyanopropyl (meth)acrylate, 2-ethyl-6-cyanohexyl (meth)acrylate, 3-cyanopropyl (meth)acrylate, hydroxyethyl (meth)acrylate, hydroxypropyl (meth)acrylate, glycidyl (meth)acrylate, and dimethylaminoethyl (meth)acrylate; crosslinking monomers such as divinylbenzene, polyethylene glycol di(meth)acrylate, polypropylene glycol di(meth)acrylate, trimethylolpropane tri(meth)acrylate, and pentaerythritol (meth)acrylate. These ethylenically unsaturated monomers can be used alone or in combination of two or more.
[0085] The content of other monomer units composed of other ethylenically unsaturated monomers in the nitrile group-containing conjugated diene copolymer is preferably 10% by weight or less, more preferably 5% by weight or less, and further preferably 3% by weight or less.
[0086] The nitrile group-containing conjugated diene copolymer is obtained by copolymerizing a monomer mixture containing the above-mentioned monomers, preferably by emulsion polymerization. As the emulsion polymerization method, a conventionally known method can be adopted.
[0087] When the monomer mixture containing the above monomers is subjected to emulsion polymerization, commonly used polymerization auxiliary materials such as emulsifiers, polymerization initiators, molecular weight regulators, etc. can be used. The method for adding these polymerization auxiliary materials is not particularly limited, and can be any method of initial one-time addition method, batch addition method, continuous addition method, etc.
[0088] There is no particular limitation on the emulsifier, and examples thereof include: nonionic emulsifiers such as polyoxyethylene alkyl ethers, polyoxyethylene alkylphenol ethers, polyoxyethylene alkyl esters, and polyoxyethylene sorbitan alkyl esters; anionic emulsifiers such as alkylbenzene sulfonates such as potassium dodecylbenzene sulfonate and sodium dodecylbenzene sulfonate, higher alcohol sulfate ester salts, and alkyl sulfosuccinates; cationic emulsifiers such as alkyltrimethylammonium chloride, dialkylammonium chloride, and benzyl ammonium chloride; copolymeric emulsifiers such as sulfoesters of α,β-unsaturated carboxylic acids, sulfates of α,β-unsaturated carboxylic acids, and sulfoalkylaryl ethers. Anionic emulsifiers are particularly preferred, alkylbenzene sulfonates are more preferred, and potassium dodecylbenzene sulfonate and sodium dodecylbenzene sulfonate are particularly preferred. These emulsifiers can be used alone or in combination of two or more. The amount of the emulsifier used is preferably 0.1 to 10 parts by weight relative to 100 parts by weight of the monomer mixture.
[0089] The polymerization initiator is not particularly limited, and examples thereof include inorganic peroxides such as sodium persulfate, potassium persulfate, ammonium persulfate, potassium perphosphate, and hydrogen peroxide; organic peroxides such as diisopropylbenzene hydroperoxide, cumene hydroperoxide, tert-butyl hydroperoxide, 1,1,3,3-tetramethylbutyl hydroperoxide, 2,5-dimethylhexane-2,5-dihydroperoxide, di-tert-butyl peroxide, di-α-isopropylbenzene peroxide, acetyl peroxide, isobutyryl peroxide, and benzoyl peroxide; azo compounds such as azobisisobutyronitrile, azobis-2,4-dimethylvaleronitrile, and methyl azobisisobutyrate. These polymerization initiators can be used alone or in combination of two or more. The amount of the polymerization initiator used is preferably 0.01 to 10 parts by weight, and more preferably 0.01 to 2 parts by weight, relative to 100 parts by weight of the monomer mixture.
[0090] In addition, the peroxide initiator can be used in combination with a reducing agent as a redox polymerization initiator. The reducing agent is not particularly limited, and examples thereof include: compounds containing metal ions in a reduced state such as ferrous sulfate and cuprous cyclohexane; sulfonic acid compounds such as sodium methanesulfonate; amine compounds such as dimethylaniline, etc. These reducing agents can be used alone or in combination of two or more. The amount of the reducing agent used is preferably 3 to 1000 parts by weight relative to 100 parts by weight of the peroxide.
[0091] The amount of water used in the emulsion polymerization is preferably 80 to 600 parts by weight, particularly preferably 100 to 200 parts by weight, based on 100 parts by weight of all monomers used.
[0092] As a method for adding monomers, for example, there can be mentioned: a method of adding the monomers to be used to the reaction container at one time; a method of adding continuously or intermittently as the polymerization proceeds; a method of adding a part of the monomers to react to a specific conversion rate, and then continuously or intermittently adding the remaining monomers to polymerize, etc. Any method can be adopted. When the monomers are mixed and added continuously or intermittently, the composition of the mixture can be fixed or it can be changed. In addition, for each monomer, the various monomers to be used can be mixed in advance and added to the reaction container, or they can be added to the reaction container separately.
[0093] Furthermore, polymerization auxiliary materials such as a chelating agent, a dispersant, a pH adjuster, a deoxidizing agent, and a particle size adjuster may be used as necessary, and the type and amount of these materials used are not particularly limited.
[0094] The polymerization temperature during emulsion polymerization is not particularly limited, but is usually 3 to 95° C., preferably 5 to 60° C. The polymerization time is about 5 to 40 hours.
[0095] When the monomer mixture is subjected to emulsion polymerization as described above and a predetermined polymerization conversion rate is reached, the polymerization system is cooled or a polymerization terminator is added to terminate the polymerization reaction. The polymerization conversion rate when the polymerization reaction is terminated is preferably 90% by weight or more, more preferably 93% by weight or more.
[0096] The polymerization terminator is not particularly limited, and examples thereof include hydroxylamine, hydroxylamine sulfate, diethylhydroxylamine, hydroxylamine sulfonic acid and its alkali metal salts, sodium dimethyldithiocarbamate, hydroquinone derivatives, catechol derivatives, aromatic hydroxydithiocarboxylic acids such as hydroxydimethylphenylthiocarboxylic acid, hydroxydiethylphenyldithiocarboxylic acid, and hydroxydibutylphenyldithiocarboxylic acid and their alkali metal salts, and alcohols such as methanol, ethanol, and isopropanol. The amount of the polymerization terminator used is preferably 0.05 to 2 parts by weight relative to 100 parts by weight of the monomer mixture.
[0097] After the polymerization reaction is terminated, unreacted monomers may be removed as desired, and the solid content concentration and pH may be adjusted to obtain a latex of a nitrile group-containing conjugated diene copolymer.
[0098] Furthermore, an anti-aging agent, a preservative, an antibacterial agent, a dispersant, etc. may be appropriately added to the latex of the nitrile group-containing conjugated diene copolymer as required.
[0099] The number average particle size of the latex of the nitrile group-containing conjugated diene copolymer is preferably 60 to 300 nm, more preferably 80 to 150 nm. The particle size can be adjusted to a desired value by adjusting the amount of the emulsifier and the polymerization initiator used.
[0100] In addition, as the conjugated diene polymer latex, as described above, a latex of natural rubber from which proteins have been removed (deproteinized natural rubber) can also be used. As the deproteinized natural rubber latex, a latex known as so-called "deproteinized natural rubber latex" obtained by a known protein removal method can be used, and the above-mentioned known protein removal method is a method of removing proteins in natural rubber latex by, for example, a protease, a surfactant, etc., and washing, centrifugation, etc.
[0101] As the conjugated diene polymer used in the present invention, as described above, synthetic polyisoprene, styrene-isoprene-styrene block copolymer (SIS), nitrile group-containing conjugated diene copolymer, deproteinized natural rubber, etc. can be used, but are not limited to these. Butadiene polymers, styrene-butadiene copolymers, etc. can also be used.
[0102] The butadiene polymer may be a homopolymer of 1,3-butadiene as a conjugated diene monomer, or a copolymer obtained by copolymerizing 1,3-butadiene as a conjugated diene monomer and another ethylenically unsaturated monomer copolymerizable therewith.
[0103] The styrene-butadiene copolymer is a copolymer obtained by copolymerizing 1,3-butadiene and styrene as conjugated diene monomers, and may be a copolymer obtained by copolymerizing other ethylenically unsaturated monomers copolymerizable with these monomers as needed.
[0104] The conjugated diene polymer latex used in the present invention may contain additives such as pH adjusters, defoamers, preservatives, chelating agents, deoxidizers, dispersants, and antioxidants that are commonly used in the latex field.
[0105] Examples of pH adjusters include alkali metal hydroxides such as sodium hydroxide and potassium hydroxide; alkali metal carbonates such as sodium carbonate and potassium carbonate; alkali metal bicarbonates such as sodium bicarbonate; ammonia; organic amine compounds such as trimethylamine and triethanolamine, etc., preferably alkali metal hydroxides or ammonia. In addition, the pH of the conjugated diene polymer latex in the preparation step is not particularly limited. In the production method of the present invention, as described later, when a xanthogenic acid compound and a sulfur-based vulcanizing agent are added to the conjugated diene polymer latex to prepare a latex composition and the latex composition is aged under prescribed conditions, the pH of the latex composition 12 hours after the start of the aging can be 9 or more.
[0106] Furthermore, in order to increase the solid content concentration of the conjugated diene polymer latex, a concentration operation may be carried out as needed by using a method such as reduced pressure distillation, atmospheric pressure distillation, centrifugal separation, membrane concentration, etc., but centrifugal separation is preferably performed from the viewpoint of being able to adjust the residual amount of the emulsifier in the conjugated diene polymer latex.
[0107] When the conjugated diene polymer latex is placed in a centrifuge, in order to improve the mechanical stability of the latex, it is preferred to add a pH adjuster to adjust the pH of the latex to 7 or higher, more preferably 9 or higher.
[0108] The solid content concentration of the conjugated diene polymer latex used in the present invention is preferably 30 to 70% by weight, more preferably 40 to 70% by weight, and further preferably 50 to 70% by weight. By making the solid content concentration within the above range, the generation of aggregates in the latex can be more effectively suppressed, and the separation of polymer particles during storage of the latex can be more effectively suppressed.
[0109] <Preparation process>
[0110] Furthermore, in the production method of the present invention, a sulfur-based vulcanizing agent and a xanthogenic acid compound are added to the above-mentioned conjugated diene polymer latex to prepare a latex composition containing them (preparation step).
[0111] The sulfur-based vulcanizing agent is not particularly limited, and examples thereof include sulfur such as powdered sulfur, sublimated sulfur, precipitated sulfur, colloidal sulfur, surface-treated sulfur, and insoluble sulfur; sulfur compounds such as sulfur chloride, sulfur dichloride, morpholine disulfide, alkylphenol disulfide, caprolactam disulfide (N,N'-disulfo-bis(hexahydro-2H-azepine-2)), phosphorus-containing polysulfide, polymer polysulfide, and 2-(4'-morpholinodisulfo)benzothiazole. Among these, sulfur can be preferably used. The sulfur-based vulcanizing agent can be used alone or in combination of two or more.
[0112] The amount of the sulfur-based vulcanizing agent used is not particularly limited, but is preferably 0.01 to 10 parts by weight, more preferably 0.01 to 3 parts by weight, further preferably 0.1 to 3 parts by weight, further preferably 0.2 to 3 parts by weight, and particularly preferably 1 to 2 parts by weight, relative to 100 parts by weight of the conjugated diene polymer contained in the latex composition. By setting the content of the sulfur-based vulcanizing agent within the above range, the occurrence of delayed hypersensitivity (IV type) symptoms in the obtained film-molded article such as the dip-molded article can be suppressed, and the tensile strength can be further improved.
[0113] The xanthate compound used in the present invention acts as a vulcanization accelerator by being used in combination with a sulfur-based vulcanizing agent. That is, when a sulfur-based vulcanizing agent is added to a latex composition, and the conjugated diene polymer in the latex composition is vulcanized by the sulfur-based vulcanizing agent to form a film-formed body such as an impregnated molded body, the xanthate compound acts as a vulcanization accelerator. In addition, in a latex composition in which a sulfur-based vulcanizing agent is added, the xanthate compound acts as a vulcanization accelerator, and after vulcanization, it is decomposed into alcohol and carbon disulfide by heat applied during vulcanization. For example, by heat applied during the manufacture of a film-formed body (heat of about 100 to 130° C. when vulcanizing a conjugated diene polymer), the xanthate compound is decomposed into alcohol and carbon disulfide, and then the components (alcohol and carbon disulfide, etc.) generated by the decomposition volatilize. As a result, the residual amount of the xanthate compound in the obtained film-formed body is reduced. That is, in the method for producing the latex composition of the present invention, a vulcanization accelerator (e.g., a dithiocarbamate-based vulcanization accelerator, a thiazole-based vulcanization accelerator, etc.) that has conventionally caused delayed hypersensitivity (type IV) symptoms is not used, but a xanthate compound is used as a vulcanization accelerator, thereby reducing the residual amount of the xanthate compound in the obtained film-molded product such as the dip-molded product, and thus, the occurrence of delayed hypersensitivity (type IV) symptoms in the obtained film-molded product can be suppressed.
[0114] The xanthogenic acid compound used in the present invention is not particularly limited, and examples thereof include xanthogenic acid, xanthogenic acid salts, xanthogenic acid disulfide (a compound in which two xanthogenic acids are bonded via a sulfur atom or the like), and xanthogenic acid polysulfide (a compound in which three or more xanthogenic acids are bonded via a sulfur atom or the like).
[0115] Xanthate is not particularly limited as long as it has a xanthate structure, and examples thereof include compounds represented by the general formula (ROC(=S)S)x-Z (wherein R is a linear or branched hydrocarbon, and Z is a metal atom. x is a number consistent with the valence of Z, and is usually 1 to 4, preferably 2 to 4, and particularly preferably 2).
[0116] The xanthate represented by the general formula (ROC(=S)S)x-Z is not particularly limited, and examples thereof include dimethyl zinc xanthate, diethyl zinc xanthate, dipropyl zinc xanthate, diisopropyl zinc xanthate, dibutyl zinc xanthate, diamyl zinc xanthate, dihexyl zinc xanthate, diheptyl zinc xanthate, dioctyl zinc xanthate, di(2-ethylhexyl) zinc xanthate, didecyl zinc xanthate, didodecyl zinc xanthate, dimethyl potassium xanthate, ethyl potassium xanthate, propyl xanthate, Xanthate, potassium isopropyl xanthate, potassium butyl xanthate, potassium amyl xanthate, potassium hexyl xanthate, potassium heptyl xanthate, potassium octyl xanthate, potassium 2-ethylhexyl xanthate, potassium decyl xanthate, potassium dodecyl xanthate, sodium methyl xanthate, sodium ethyl xanthate, sodium propyl xanthate, sodium isopropyl xanthate, sodium butyl xanthate, sodium amyl xanthate, sodium hexyl xanthate, sodium heptyl xanthate, sodium octyl xanthate, sodium 2-ethylhexyl xanthate, sodium decyl xanthate, sodium dodecyl xanthate, etc. Among these, xanthate in the general formula (ROC(=S)S)x-Z is preferably 2 or more, isopropyl xanthate and butyl xanthate are more preferred, and diisopropyl zinc xanthate and dibutyl zinc xanthate are particularly preferred. These xanthates may be used alone or in combination of two or more.
[0117] Xanthogenic acid disulfide is a compound in which two xanthogenic acids are bonded via a sulfur atom or the like. It is not particularly limited and examples thereof include dimethyl xanthogenic acid disulfide, diethyl xanthogenic acid disulfide, diisopropyl xanthogenic acid disulfide, dibutyl xanthogenic acid disulfide, polymethyl xanthogenic acid sulfide, polyethyl xanthogenic acid sulfide, polyisopropyl xanthogenic acid sulfide, and polybutyl xanthogenic acid sulfide. Among these, diisopropyl xanthogenic acid disulfide and dibutyl xanthogenic acid disulfide are preferred.
[0118] Polysulfide xanthogenic acid is a compound in which three or more xanthogenic acids are bonded via a sulfur atom or the like, and examples thereof include trisulfide xanthogenic acid in which three xanthogenic acids are bonded via sulfur, tetrasulfide xanthogenic acid in which four xanthogenic acids are bonded via sulfur, and pentasulfide xanthogenic acid in which five xanthogenic acids are bonded via sulfur.
[0119] In addition, these xanthate compounds may be contained in the latex composition alone, or preferably in two or more forms. For example, when xanthate is added to the latex composition, a portion of the added xanthate exists in the form of a xanthate, and as a result, two or more xanthate compounds may be contained in the latex composition. Alternatively, a portion of the xanthate added to the latex composition may exist in the form of xanthate disulfide or xanthate polysulfide through the action of the sulfur-based vulcanizing agent in the latex composition. Similarly, even when xanthate, xanthate disulfide or xanthate polysulfide are added to the latex composition, these may exist in the form of any one of xanthate, xanthate, xanthate disulfide or xanthate polysulfide, respectively.
[0120] The amount of the xanthogenic acid compound used (when a plurality of xanthogenic acid compounds are included, the total amount used) is not particularly limited, but is preferably 0.01 to 10 parts by weight, more preferably 0.1 to 7 parts by weight, further preferably 0.5 to 5 parts by weight, and further preferably 1 to 3 parts by weight, relative to 100 parts by weight of the conjugated diene polymer contained in the latex. When the amount of the xanthogenic acid compound used is within the above range, the occurrence of delayed hypersensitivity (IV type) symptoms can be suppressed in the obtained film-molded article, such as the dip-molded article, and the tensile strength can be further improved.
[0121] In the present invention, it is preferred that the latex composition contains substantially no compound conventionally used as a vulcanization accelerator other than the xanthic acid compound, specifically, a sulfur-containing vulcanization accelerator (e.g., a dithiocarbamate-based vulcanization accelerator, a thiazole-based vulcanization accelerator, etc.) which causes delayed hypersensitivity (type IV) symptoms and which remains in the obtained film-molded body such as the dip-molded body after having functioned as a vulcanization accelerator.
[0122] Furthermore, in the production method of the present invention, a strong acid salt-based surfactant may be added to the above-mentioned conjugated diene polymer latex in addition to the sulfur-based vulcanizing agent and the xanthogenic acid compound as needed.
[0123] As strong acid salt surfactant, there is no particular limitation as long as it has a structure of a salt composed of a strong acid and a strong base and has a surface active effect, and examples thereof include compounds having a sulfonate group, compounds having a sulfate group or a sulfate ester group, compounds having a phosphate group or a phosphate ester group, compounds having a nitrate group, etc. Among these, compounds having a sulfonate group, compounds having a phosphate group or a phosphate ester group are preferred. In addition, these strong acid salt surfactants can be used alone or in combination of multiple types.
[0124] The compound having a sulfonate group as the strong acid salt-based surfactant is not particularly limited as long as it is a compound having a salt structure in which a sulfonic group is neutralized by a strong base, and examples thereof include sodium salt of β-naphthalenesulfonic acid formaldehyde condensate (NASF), sodium alkylbenzenesulfonate, sodium 1-hexanesulfonate, trisodium naphthalenetrisulfonate, and the like.
[0125] The compound having a sulfate group or a sulfate ester salt group as the strong acid salt-based surfactant is not particularly limited as long as it is a compound having a salt structure in which the sulfate group or the sulfate ester group is neutralized by a strong base, and examples thereof include sodium lauryl sulfate.
[0126] The compound having a phosphate group or a phosphate ester group as the strong acid salt-based surfactant is not particularly limited as long as it has a salt structure in which the phosphate group or the phosphate ester group is neutralized by a strong base, and examples thereof include sodium lauryl phosphate and potassium lauryl phosphate.
[0127] In addition, as a strong acid salt surfactant, it is also possible to have a compound with a polycyclic structure. As a polycyclic structure, as long as there are two or more ring structures, it is not particularly limited, and for example, a biphenyl structure as a structure in which two benzene rings are connected by a single bond, a condensed polycyclic structure formed by condensing (contracting) two or more monocyclic rings, etc. can be cited. The ring constituting the polycyclic structure can be either an alicyclic ring or an aromatic ring, and in addition, it can also be a ring containing heteroatoms. In addition, the number of rings is not particularly limited, and is preferably more than two rings, and from practicality, its upper limit is about ten rings. As a condensed polycyclic structure, for example: dicyclopentadiene structure, naphthalene structure, fluorene structure, anthracene structure, phenanthrene structure, triphenylene structure, pyrene structure, ovalbenzene structure, etc. can be cited.
[0128] Examples of strong acid salt-based surfactants having a polycyclic structure include β-naphthalenesulfonic acid formaldehyde condensate sodium salt (NASF), sodium naphthalenesulfonate, disodium naphthalene disulfonate, trisodium naphthalene trisulfonate, sodium butyl naphthalene sulfonate, etc. Among these, β-naphthalenesulfonic acid formaldehyde condensate sodium salt (NASF) which is a compound having a sulfonate group and a polycyclic structure is preferred.
[0129] The usage amount of the strong acid salt surfactant is preferably 0.01 to 5 parts by weight, more preferably 0.1 to 4 parts by weight, further preferably 0.5 to 3 parts by weight, and further preferably 0.8 to 1.5 parts by weight relative to 100 parts by weight of the conjugated diene polymer contained in the conjugated diene polymer latex. By making the usage amount of the strong acid salt surfactant within the above range, the tensile strength, tensile elongation, and tear strength of the obtained film-formed bodies such as the impregnated bodies can be further improved. In addition, when preparing the conjugated diene polymer latex, when a strong acid salt surfactant is used as an emulsifier, the above usage amount is the amount after removing the amount of the strong acid salt surfactant used as the emulsifier.
[0130] That is, for example, as a conjugated diene polymer latex, a solution or fine suspension of a conjugated diene polymer is emulsified in water in the presence of an emulsifier, the organic solvent is removed as needed, and the solid content concentration is adjusted to 30 to 70% by weight (more preferably 40 to 70% by weight, further preferably 50 to 70% by weight) by concentration, thereby obtaining a conjugated diene polymer latex. When using the conjugated diene polymer latex, it is preferred that the amount of the strong acid salt surfactant used after removing the organic solvent and adjusting the solid content concentration to 30 to 70% by weight (more preferably 40 to 70% by weight, further preferably 50 to 70% by weight) is within the above-mentioned range.
[0131] As a method for adding a sulfur-based vulcanizing agent and a xanthate compound to the above-mentioned conjugated diene polymer latex, there is no particular limitation, and they can be added in the order of the sulfur-based vulcanizing agent and the xanthate compound, or they can be added simultaneously. In addition, in the case where a strong acid salt surfactant is further added to the conjugated diene polymer latex in addition to the sulfur-based vulcanizing agent and the xanthate compound, as its adding method, there is no particular limitation, and they can be added in the order of the sulfur-based vulcanizing agent, the xanthate compound, and the strong acid salt surfactant, or they can be added simultaneously. Alternatively, after the strong acid salt surfactant is added in advance, it is also possible to add in the order of the sulfur-based vulcanizing agent and the xanthate compound, or in the order of the xanthate compound and the sulfur-based vulcanizing agent. In particular, from the viewpoint of being able to make a latex composition with better stability even if the pH of the latex composition is reduced due to the addition of the xanthate compound, it is preferred to adopt a method of adding a sulfur-based vulcanizing agent and a xanthate compound after the strong acid salt surfactant is added in advance. In addition, the order of adding the sulfur-based vulcanizing agent and the xanthogenic acid compound is not particularly limited, and one of them may be added first, or they may be added simultaneously. In addition, the sulfur-based vulcanizing agent, the xanthogenic acid compound, and the strong acid salt surfactant may be added in the form of an aqueous solution or an aqueous dispersion.
[0132] Furthermore, in the production method of the present invention, in addition to adding the sulfur-based vulcanizing agent and the xanthogenic acid compound to the above-mentioned conjugated diene polymer latex, an activator may be added as needed.
[0133] By adding an activator to the latex composition, when the conjugated diene polymer in the latex composition is vulcanized using a sulfur-based vulcanizing agent to prepare a film-formed product such as a dip-formed product, the activator acts as a vulcanization accelerator together with the above-mentioned xanthogenic acid compound, thereby further improving the tear strength of the obtained film-formed product such as the dip-formed product.
[0134] As activator, it is not particularly limited. From the viewpoint of further improving the tear strength of film-molded bodies such as the obtained impregnated body, it is preferred to use a metal compound. As metal compound, it is not particularly limited. For example, metal oxides, metal compounds containing at least one carbon atom, etc. can be cited. As the metal constituting the metal compound, it is not particularly limited. Main group metals (at least one element selected from the 1st group element, the 2nd group element, the 12th group element, the 13th group element, the 14th group element, the 15th group element, the 16th group element, the 17th group element and the 18th group element) are preferred, and 2nd group element, 12th group element, 13th group element, and 14th group element are more preferred. Zinc, magnesium, calcium, aluminum, and lead are further preferred. Zinc, magnesium, and calcium are particularly preferred, and zinc is most preferred. These metal compounds can be used alone or in combination.
[0135] The metal oxide is not particularly limited, but from the viewpoint of further improving the tear strength of the obtained film-molded body such as the dip-molded body, zinc oxide, magnesium oxide, titanium oxide, calcium oxide, lead oxide, iron oxide, copper oxide, tin oxide, nickel oxide, chromium oxide, cobalt oxide, and aluminum oxide are preferred, and zinc oxide is more preferred.
[0136] As the metal compound containing at least one carbon atom, carbonates, bicarbonates, hydroxides, and organometallic compounds are preferred from the viewpoint of further improving the tear strength of the obtained film-formed body such as the impregnated body, and carbonates, bicarbonates, and organometallic compounds are more preferred. Among these, inorganic salts such as carbonates and bicarbonates are particularly preferred from the viewpoint of excellent stability of the compound itself and excellent ease of acquisition.
[0137] The amount of the activator used is preferably 0.01 to 10 parts by weight, more preferably 0.1 to 5 parts by weight, and even more preferably 1 to 3 parts by weight relative to 100 parts by weight of the conjugated diene polymer contained in the latex composition. By setting the amount of the activator used within the above range, the tear strength of the obtained film-molded body such as the impregnated body can be further improved.
[0138] The method for blending the activator is not particularly limited as long as it is a method that ultimately results in a state where the conjugated diene polymer latex and the activator are mixed.
[0139] Furthermore, a vulcanization accelerator may be further added to the latex composition within a range that can suppress the occurrence of delayed hypersensitivity (type IV) symptoms in the obtained film-molded article or the like.
[0140] As the vulcanization accelerator, a vulcanization accelerator commonly used in dip molding can be used, and examples thereof include dithiocarbamic acids such as diethyldithiocarbamic acid, dibutyldithiocarbamic acid, di-2-ethylhexyldithiocarbamic acid, dicyclohexyldithiocarbamic acid, diphenyldithiocarbamic acid, and dibenzyldithiocarbamic acid, and zinc salts thereof; 2-mercaptobenzothiazole, 2-mercaptobenzothiazole zinc, 2-Mercaptothiazoline, dibenzothiazyl disulfide, 2-(2,4-dinitrophenylthio)benzothiazole, 2-(N,N-diethylthiocarbamoylthio)benzothiazole, 2-(2,6-dimethyl-4-morpholinothio)benzothiazole, 2-(4'-morpholinodithio)benzothiazole, 4-morpholino-2-benzothiazole disulfide, 1,3-bis(2-benzothiazolylmercaptomethyl)urea, etc. The vulcanization accelerator can be used alone or in combination of two or more.
[0141] Furthermore, the latex composition may further contain the following compounding agents as needed: an anti-aging agent; a dispersant; a reinforcing agent such as carbon black, silica, talc, etc.; a filler such as calcium carbonate, clay, etc.; an ultraviolet absorber; a plasticizer, etc.
[0142] Examples of the antioxidant include phenolic antioxidants not containing sulfur atoms, such as 2,6-di-4-methylphenol, 2,6-di-tert-butylphenol, butylhydroxyanisole, 2,6-di-tert-butyl-α-dimethylamino-p-cresol, octadecyl-3-(3,5-di-tert-butyl-4-hydroxyphenyl) propionate, styrenated phenol, 2,2'-methylene-bis(6-α-methylbenzyl-p-cresol), 4,4'-methylenebis(2,6-di-tert-butylphenol), 2,2'-methylenebis(4-methyl-6-tert-butylphenol), alkylated bisphenols, and butylated reaction products of p-cresol and dicyclopentadiene; 2,2'-thiobis-(4-methyl-6-tert-butylphenol), 4,4'-thiobis-(6-tert-butyl-o-cresol), 2,6-di-tert-butyl Thiobisphenol antioxidants such as tris(nonylphenyl) phosphite, diphenyl isodecyl phosphite, tetraphenyl dipropylene glycol diphosphite, etc.; phosphite antioxidants such as dimethylsilyl thiodipropionate, etc.; amine antioxidants such as phenyl-α-naphthylamine, phenyl-β-naphthylamine, p-(p-toluenesulfonylamino)diphenylamine, 4,4'-(α,α-dimethylbenzyl)diphenylamine, N,N-diphenyl-p-phenylenediamine, N-isopropyl-N'-phenyl-p-phenylenediamine, butyraldehyde-aniline condensate, etc.; quinoline antioxidants such as 6-ethoxy-2,2,4-trimethyl-1,2-dihydroquinoline, etc.; hydroquinone antioxidants such as 2,5-di-tert-amylhydroquinone, etc. These anti-aging agents can be used alone or in combination of two or more.
[0143] The content of the antioxidant is preferably 0.05 to 10 parts by weight, more preferably 0.1 to 5 parts by weight, and even more preferably 1 to 3 parts by weight, based on 100 parts by weight of the conjugated diene polymer.
[0144] There are no particular limitations on the method of mixing various compounding agents in the latex composition, and examples thereof include: after obtaining a composition containing a conjugated diene polymer latex, a sulfur-based vulcanizing agent, and a xanthate compound as described above, using a dispersing machine such as a ball mill, a kneader, and a disperser, various compounding agents to be mixed as needed in the obtained composition; after obtaining a composition containing a conjugated diene polymer latex and a strong acid salt-based surfactant, using the above-mentioned dispersing machine, preparing an aqueous dispersion of compounding components other than the conjugated diene polymer latex and the strong acid salt-based surfactant, and then mixing the aqueous dispersion with the latex composition containing the conjugated diene polymer latex and the strong acid salt-based surfactant, etc. In addition, at least a part of the various compounding agents may also be mixed after aging as described later.
[0145] The solid content concentration of the latex composition of the present invention is preferably 10 to 60% by weight, more preferably 10 to 55% by weight.
[0146] The pH of the latex composition before aging obtained in the preparation process of the present invention is preferably 10 or more, more preferably 11 or more, and even more preferably 12 or more. By setting the pH of the latex composition before aging to be within the above range, the stability of the latex composition after aging can be further improved. The upper limit of the pH of the latex composition before aging is not particularly limited, but is preferably 14 or less, and more preferably 13.5 or less.
[0147] <Aging process>
[0148] In the present invention, the latex composition prepared in this way is aged (preliminary crosslinking). Aging can be performed by storing at a temperature of 5 to 60° C. for 12 hours to 14 days.
[0149] The aging temperature is 5 to 60° C., preferably 10 to 30° C., and more preferably 10 to 25° C. When the aging temperature is too low, the mechanical properties of the obtained impregnated molded body or other film-shaped body are insufficient. On the other hand, when the aging temperature is too high, the tensile strength of the obtained impregnated molded body or other film-shaped body is reduced.
[0150] The aging time depends on the aging temperature, but is 12 hours to 14 days, preferably 12 hours to 10 days, and more preferably 12 hours to 7 days. When the aging time is too short, the mechanical properties of the obtained film-shaped body such as the impregnated body are insufficient. On the other hand, when the aging time is too long, the tensile strength of the obtained film-shaped body such as the impregnated body is reduced.
[0151] In the present invention, the pH of the latex composition 12 hours after the start of aging is set to 9 or more, preferably 9.5 or more, and more preferably 10 or more in the aging step. If the pH of the latex composition 12 hours after the start of aging is lower than the above range, the stability of the obtained latex composition is poor. In addition, the pH of the latex composition tends to gradually decrease due to aging from the start of aging, but it is preferred that the pH of the latex composition continue to be maintained at 9 or more from the start of aging to the end of aging, and it is more preferred that the pH continue to be maintained at the above pH.
[0152] Here, in the present invention, by making the conjugated diene polymer latex contain a sulfur-based vulcanizing agent and a xanthogenic acid compound, since the xanthogenic acid compound does not cause delayed hypersensitivity (type IV), the occurrence of delayed hypersensitivity (type IV) can be effectively suppressed. On the other hand, the present inventors have found that when the latex composition containing the xanthogenic acid compound is aged (pre-crosslinked) and then used to produce a film-formed body such as a dip-formed body, there is a problem that the amount of coagulation in the latex composition increases, making it difficult to perform dip molding. In particular, since a conjugated diene polymer that does not contain a carboxyl group is used as the conjugated diene polymer latex, this problem tends to become more significant.
[0153] In this regard, the present inventors have conducted in-depth research and found that when the latex composition is matured, the pH of the latex composition is set to 9 or more after 12 hours from the start of the maturation, which can effectively solve such problems. In particular, after in-depth research, the present inventors found that when a xanthate compound is added to a conjugated diene polymer latex, the pH decreases when the resulting latex composition is matured (pre-crosslinked). The decrease in pH during maturation is a unique phenomenon observed when a xanthate compound is added. Although not limited to a specific theory, it can be considered that one of the reasons for the decrease in pH during the maturation process is the decomposition of the xanthate compound. It can be considered that due to the decrease in pH, the stability of the latex composition will be impaired, resulting in an increase in the amount of coagulants in the latex composition. In this regard, the present invention has found that the above-mentioned problem can be solved by setting the pH of the latex composition to 9 or more after 12 hours from the start of the maturation.
[0154] As described above, the method for making the pH of the latex composition 12 hours after the start of aging to 9 or more is not particularly limited, and examples thereof include a method of making the pH of the latex composition before aging to 11 or more in the preparation process, and a method of adding a pH adjuster to the latex composition during aging.
[0155] In the present invention, the pH of the latex composition 12 hours after the start of aging may be 9 or more. The pH of the latex composition after aging is not particularly limited, but is preferably 9 or more, more preferably 9.5 or more, and even more preferably 10 or more. By setting the pH of the latex composition after aging to be within the above range, the stability of the obtained latex composition can be further improved. The upper limit of the pH of the latex composition after aging is not particularly limited, but is preferably 14 or less, and more preferably 13.5 or less.
[0156] In the present invention, the pH can be adjusted to the above range by adding a pH adjuster to the latex composition after or during aging. The timing of adding the pH adjuster to the latex composition after or during aging is not particularly limited, but it is preferably added within 24 hours from the start of aging. From the viewpoint of making the pH of the latex composition 12 hours after the start of aging as high as possible, it is more preferably added within 12 hours from the start of aging. Considering that the pH of the latex composition tends to gradually decrease from the start of aging, it is further preferably added within 1 hour from the start of aging.
[0157] The pH adjuster added to the latex composition after or during aging is not particularly limited, and examples thereof include: alkali metal hydroxides such as sodium hydroxide and potassium hydroxide; alkali metal carbonates such as sodium carbonate and potassium carbonate; alkali metal bicarbonates such as sodium bicarbonate; ammonia; organic amine compounds such as trimethylamine and triethanolamine, etc., but alkali metal hydroxides, ammonia or organic amine compounds are preferred. These pH adjusters can be used alone or in combination of two or more.
[0158] According to the method for producing a latex composition of the present invention, the latex composition before aging contains a conjugated diene polymer latex, a sulfur-based vulcanizing agent, and a xanthate compound. The latex composition before aging is aged so that the pH of the latex composition 12 hours after the start of aging is 9 or more, thereby making the stability of the latex composition itself excellent, and at the same time making the obtained film-molded products such as dip-molded products suppress the symptoms of delayed hypersensitivity (type IV) and have excellent tensile strength, tensile elongation, and tear strength.
[0159] <Impregnation molding>
[0160] In the method for producing a dip-molded article of the present invention, a dip-molded article can be obtained by dip-molding a latex composition obtained by the above-mentioned method of the present invention. The dip-molding method is as follows: a mold is dipped into a latex composition, the composition is deposited on the surface of the mold, and then, after the mold is lifted from the composition, the composition deposited on the surface of the mold is dried. In addition, the mold before being dipped in the latex composition can be preheated. In addition, before dipping the mold in the latex composition or after the mold is lifted from the latex composition, a coagulant can be used as needed.
[0161] Specific examples of the method of using the coagulant include a method in which the mold before being immersed in the latex composition is immersed in a solution of the coagulant so that the coagulant adheres to the mold (anodic coagulation immersion method), a method in which the mold on which the latex composition is deposited is immersed in a coagulant solution (Teague coagulation immersion method), etc. However, from the viewpoint of obtaining an immersion-molded body with less uneven thickness, the anodic coagulation immersion method is preferred.
[0162] Specific examples of the coagulant include metal halides such as barium chloride, calcium chloride, magnesium chloride, zinc chloride, and aluminum chloride; nitrates such as barium nitrate, calcium nitrate, and zinc nitrate; acetates such as barium acetate, calcium acetate, and zinc acetate; and sulfates such as calcium sulfate, magnesium sulfate, and aluminum sulfate. Calcium salts are particularly preferred, and calcium nitrate is more preferred. These water-soluble multivalent metal salts can be used alone or in combination of two or more.
[0163] The coagulant can be used as an aqueous solution, an alcohol solution or a mixture thereof, and is preferably used in the form of an aqueous solution. The aqueous solution may further contain a water-soluble organic solvent such as methanol or ethanol, and a nonionic surfactant. The concentration of the coagulant varies depending on the type of the water-soluble multivalent metal salt, but is preferably 5 to 50% by weight, more preferably 10 to 30% by weight.
[0164] After the mold is lifted from the latex composition, it is usually heated to dry the deposit formed on the mold. The drying conditions can be appropriately selected.
[0165] Next, heating is performed to crosslink the dip-molded layer formed on the mold. The crosslinking of the dip-molded layer can usually be performed by performing a heat treatment at a temperature of 80 to 150°C, preferably for 10 to 130 minutes. As a heating method, a method of external heating using infrared rays or hot air or internal heating using high-frequency waves can be adopted. External heating using hot air is particularly preferred. In addition, before the heat treatment is performed, the dip-molded layer can be immersed in water, preferably in warm water at 30 to 70°C, for about 1 to 60 minutes to remove water-soluble impurities (such as residual emulsifiers, coagulants, etc.). The removal operation of water-soluble impurities can be performed after the dip-molded layer is subjected to a heat treatment, but from the perspective of being able to remove water-soluble impurities more efficiently, it is preferably performed before the heat treatment.
[0166] Then, the dip-molded body can be obtained by separating the dip-molded layer from the dip-molding die. As a method of separation, it is possible to adopt a method of peeling it from the molding die by hand, or peeling it by pressure of water or compressed air. In addition, after the separation, it can be further heated at a temperature of 60 to 120° C. for 10 to 120 minutes.
[0167] The film thickness of the dip-molded body is preferably 0.03 to 0.50 mm, more preferably 0.05 to 0.40 mm, particularly preferably 0.08 to 0.30 mm.
[0168] The dip molded article obtained by the production method of the present invention is obtained by using the above-mentioned latex composition, so the delayed hypersensitivity (IV type) symptoms can be suppressed, and the tensile strength, tensile elongation, and tear strength are also excellent, and it can be particularly preferably used as a glove. In the case where the film molded article is a glove, in order to prevent the film molded articles from being closely attached to each other at the contact surface and to improve the lubricity when putting on and taking off, inorganic fine particles such as talc and calcium carbonate or organic fine particles such as starch particles may be sprinkled on the surface of the glove, or an elastic layer containing fine particles may be formed on the surface of the glove, and the surface layer of the glove may be chlorinated.
[0169] Furthermore, the dip-molded article obtained by the production method of the present invention can be used for medical products such as nipples for baby bottles, glass straws, tubes, cold water pads, inflatable air bags, medical catheters, condoms, etc., toys such as balloons, dolls, balls, etc., industrial products such as bags for pressurized molding and gas storage bags, finger cots, etc., in addition to the above-mentioned gloves.
[0170] Example
[0171] Hereinafter, the present invention will be described in detail by way of examples, but the present invention is not limited to these examples. In addition, unless otherwise specified, the following "parts" are weight references. In addition, various physical properties are measured in the following manner.
[0172] <Solid content concentration>
[0173] 2 g of the sample (weight: X2) was accurately weighed in an aluminum pan (weight: X1) and dried in a hot air dryer at 105°C for 2 hours. After cooling in the dryer, the weight of the sample together with the aluminum pan was measured (weight: X3), and the solid content concentration was calculated according to the following calculation formula.
[0174] Solid content concentration (weight %) = (X3-X1) × 100 / X2
[0175] <Content of aggregates>
[0176] The solid content concentration of the latex composition is measured according to the above method. After accurately weighing about 100 g of the latex composition, it is filtered through a 200-mesh SUS metal mesh of known weight, and the coagulation on the metal mesh is washed with water several times to remove the latex composition. After drying it at 105°C for 60 minutes, its dry weight is measured, and the content of the coagulation is calculated as a ratio when the amount of the polymer component contained in the latex composition is 100% by weight (unit: weight %). The less the content of the coagulation, the better the stability of the latex composition.
[0177] <Appearance of Dip-molded Article>
[0178] The dip-molded body was visually checked for the presence or absence of adhesion of aggregates.
[0179] <Tensile strength and tensile elongation of dip-molded articles>
[0180] Based on ASTM D412, the impregnated molded body was punched out with a dumbbell cutter (trade name "Super Dumbbell (model: SDMK-100C)", manufactured by DUMBBELL Co., Ltd.) to prepare a test piece for tensile strength measurement. The test piece was stretched at a tensile speed of 500 mm / min using a universal tensile testing machine (trade name "RTG-1210", manufactured by ORIENTEC Co., Ltd.) to measure the tensile strength just before breaking (unit: MPa) and the tensile elongation just before breaking (unit: %).
[0181] <Tear Strength of Dip Molded Article>
[0182] Based on ASTM D624-00, the impregnated molded body was placed in a constant temperature and humidity chamber at 23°C and a relative humidity of 50% for more than 24 hours, and then punched out with a dumbbell cutter (trade name "Die C", manufactured by DUMBBEL Co., Ltd.) to prepare a test piece for measuring tear strength. The test piece was stretched at a tensile speed of 500 mm / min using a universal tensile testing machine (trade name "RTG-1210", manufactured by A&D Co., Ltd.) to measure the tear strength (unit: N / mm).
[0183] <Example 1>
[0184] (Production of Latex of Synthetic Polyisoprene (A-1))
[0185] 900 parts of n-hexane and 100 parts of isoprene were placed in a dry, nitrogen-substituted autoclave with a stirrer. The temperature in the autoclave was set to 60°C, and while stirring, 0.05 parts of a n-hexane solution containing 15% by weight of n-butyl lithium was added as a catalyst solution, and the mixture was reacted for 1 hour to obtain a reaction solution. The polymerization reaction rate was 99%. Methanol was added to the obtained reaction solution as a polymerization terminator to stop the reaction, thereby obtaining a n-hexane solution (a-1) of synthetic polyisoprene with a weight average molecular weight (Mw) of 1,840,000 (solid content concentration 10% by weight).
[0186] On the other hand, potassium rosinate was added to water and the temperature was raised to 60° C. to dissolve the potassium rosinate, thereby preparing an emulsifier aqueous solution (b-1) having a concentration of 1.5% by weight.
[0187] Next, the n-hexane solution of synthetic polyisoprene (a-1) and the aqueous emulsifier solution (b-1) obtained above were mixed using a mixer (product name "Multi-channel mixer MS26-MMR-5.5L", manufactured by Satake Chemical Machinery Co., Ltd.) so that the amount of synthetic polyisoprene in the n-hexane solution of synthetic polyisoprene (a-1) and the amount of potassium rosinate in the aqueous emulsifier solution (b-1) were 10 parts per 100 parts, and then mixed and emulsified at a rotation speed of 4100 rpm using an emulsifier (product name "Milder MDN310", manufactured by Pacific Machinery Co., Ltd.), thereby obtaining an emulsified dispersion (c-1). In this case, the total feed flow rate of the n-hexane solution of synthetic polyisoprene (a-1) and the aqueous emulsifier solution (b-1) was 2000 kg / hr, the temperature was 60°C, and the back pressure (gauge pressure) was 0.5 MPa.
[0188] Next, the obtained emulsified dispersion (c-1) was heated to 80°C under a reduced pressure of -0.01 to -0.09 MPa (gauge pressure), and the n-hexane was distilled off to obtain an aqueous dispersion (d-1) of synthetic polyisoprene. At this time, a defoamer (trade name "SM5515", manufactured by Dow Corning Toray Co., Ltd.) was continuously added while spraying so that the amount of the defoamer was 300 ppm by weight relative to the synthetic polyisoprene in the emulsified dispersion (c-1). In addition, when the n-hexane was distilled off, the emulsified dispersion (c-1) was adjusted to less than 70% by volume of the tank volume, and a three-stage inclined paddle blade was used as a stirring blade, and stirring was slowly carried out at 60 rpm.
[0189] After the distillation of n-hexane was completed, the obtained aqueous dispersion of synthetic polyisoprene (d-1) was centrifuged at 8000 to 9000 G using a continuous centrifuge (product name "SRG510", manufactured by Alfa Laval) to concentrate the aqueous dispersion, thereby obtaining a latex of synthetic polyisoprene (A-1) having a solid content concentration of 60% by weight as a light liquid. The centrifugal separation was performed under the following conditions: the solid content concentration of the aqueous dispersion (d-1) before centrifugation was 8% by weight, the flow rate during the continuous centrifugation was 1300 kg / hr, and the back pressure (gauge pressure) of the centrifuge was 0.1 MPa. In addition, in the obtained latex of synthetic polyisoprene (A-1), potassium rosinate remained in an amount of 1 part per 100 parts of the synthetic polyisoprene (A-1) in the latex of synthetic polyisoprene (A-1). In addition, the synthetic polyisoprene (A-1) contained substantially no carboxyl group.
[0190] (Preparation of latex composition)
[0191] While stirring the latex of the synthetic polyisoprene (A-1) obtained above, sodium salt of β-naphthalenesulfonic acid formaldehyde condensate (NASF, product name "DEMOL T-45", manufactured by Kao Corporation) as a strong acid salt-based surfactant was added so that the amount of the sodium salt of β-naphthalenesulfonic acid formaldehyde condensate in terms of solid content was 1.0 part per 100 parts of the synthetic polyisoprene (A-1) in the latex of the synthetic polyisoprene (A-1). Then, while stirring the obtained mixture, an aqueous dispersion of each compounding ingredient was added so that, based on the solid content conversion amount, 2.5 parts of diisopropyl zinc xanthate as a xanthogenic acid compound, 1.5 parts of zinc oxide, 1.5 parts of sulfur, and 2 parts of an antioxidant (product name "Wingstay L", manufactured by Goodyear Co., Ltd.) were present with respect to 100 parts of the synthetic polyisoprene (A-1) in the mixture, and then an aqueous potassium hydroxide solution (concentration 5.0% by weight) was added to obtain a latex composition whose pH was adjusted to 12.5 (the pH of the latex composition before aging was adjusted to 12.5).
[0192] (Maturation of latex composition)
[0193] Then, the obtained latex composition was aged for 48 hours in a constant temperature water tank adjusted to 30°C. In addition, a potassium hydroxide aqueous solution (concentration 5.0 weight%) was added to the latex composition 12 hours after the start of aging to adjust the pH of the latex composition to 12.1. In addition, 12 hours after the start of aging, the pH of the latex composition before the addition of the potassium hydroxide aqueous solution was 11.6, and the pH of the latex composition after aging for 48 hours was 11.8.
[0194] In addition, the pH of the latex composition during aging gradually decreases from the start of aging to 12 hours later, and becomes the pH of the latex composition after 12 hours of aging (the same applies to each of the examples and comparative examples described later). That is, the pH of the latex composition during aging is maintained at or above the pH of the latex composition after aging for 12 hours. For example, in Example 1, the pH of the latex composition at the start of aging is 12.6, and the pH gradually decreases due to aging, and the pH of the latex composition 12 hours after the start of aging is 11.6. That is, in Example 1, the pH of the latex composition continues to be maintained at or above 11.6 from the start of aging to 12 hours later.
[0195] (Manufacturing of Impregnated Molded Article)
[0196] A commercially available ceramic hand-shaped mold (manufactured by Shinko Corporation) was cleaned, preheated in an oven at 70°C, and then immersed in a coagulant aqueous solution containing 18% by weight of calcium nitrate and 0.05% by weight of polyoxyethylene lauryl ether (trade name "Emulgen 109P", manufactured by Kao Corporation) for 5 seconds, and then taken out of the coagulant aqueous solution. Next, the hand-shaped mold was dried in an oven at 70°C for more than 30 minutes, thereby allowing the coagulant to adhere to the hand-shaped mold and cover the hand-shaped mold with the coagulant.
[0197] Then, the hand-shaped mold covered with the coagulant is taken out of the oven and immersed in the latex composition obtained after aging for 48 hours for 10 seconds. Next, the hand-shaped mold is air-dried at room temperature for 10 minutes, and then immersed in warm water at 60°C for 5 minutes to dissolve water-soluble impurities and form a dip-molded layer on the hand-shaped mold. Then, the dip-molded layer formed on the hand-shaped mold is heated in an oven at a temperature of 130°C for 30 minutes to cross-link it, and then cooled to room temperature, sprinkled with talc, and peeled off from the hand-shaped mold to obtain a dip-molded body (rubber glove). Then, according to the above method, the obtained dip-molded body (rubber glove) is evaluated for the coagulant content, appearance, tensile strength, tensile elongation, and tear strength. The results are shown in Table 1. In addition, the appearance of the obtained dip-molded body (rubber glove) is good and there are no special problems (the same is true in the examples described later).
[0198] <Example 2>
[0199] A latex composition before aging having a pH of 11.1 was obtained in the same manner as in Example 1 except that the amount of the pH adjuster (potassium hydroxide aqueous solution) added to the latex composition before aging was changed. Then, the obtained latex composition before aging was aged for 48 hours in the same manner as in Example 1. In addition, in Example 2, a potassium hydroxide aqueous solution (concentration 5.0% by weight) was added to the latex composition 12 hours after the start of aging to adjust the pH of the latex composition to 11.0. In addition, 12 hours after the start of aging, the pH of the latex composition before the addition of the potassium hydroxide aqueous solution was 10.4, and the pH of the latex composition after aging for 48 hours was 10.8. Then, using the latex composition after aging for 48 hours, a dip molded body (rubber glove) was produced in the same manner as in Example 1, and was evaluated in the same manner. The results are shown in Table 1.
[0200] <Example 3>
[0201] A latex composition before aging having a pH of 11.1 was obtained in the same manner as in Example 1 except that the amount of the pH adjuster (potassium hydroxide aqueous solution) added relative to the latex composition before aging was changed. Then, the obtained latex composition before aging was aged for 48 hours in the same manner as in Example 1. In addition, in Example 3, no pH adjuster (potassium hydroxide aqueous solution) was added to the latex composition 12 hours after the start of aging. In addition, the pH of the latex composition 12 hours after the start of aging was 10.4, and the pH of the latex composition after aging was 10.1. Then, using the latex composition after aging for 48 hours, a dip molded body (rubber glove) was manufactured in the same manner as in Example 1, and was evaluated in the same manner. The results are shown in Table 1.
[0202] <Example 4>
[0203] A latex composition before aging having a pH of 11.1 was obtained in the same manner as in Example 1 except that sodium salt of β-naphthalenesulfonic acid formaldehyde condensate (NASF) was not added to the latex composition before aging and the amount of the pH adjuster (potassium hydroxide aqueous solution) added relative to the latex composition before aging was changed. Then, the obtained latex composition before aging was aged for 48 hours in the same manner as in Example 1. In addition, in Example 4, no pH adjuster (potassium hydroxide aqueous solution) was added to the latex composition after 12 hours from the start of aging. In addition, the pH of the latex composition after 12 hours from the start of aging was 10.5, and the pH of the latex composition after aging was 10.2. Then, using the latex composition after aging for 48 hours, a dip molded body (rubber glove) was manufactured in the same manner as in Example 1 and evaluated in the same manner. The results are shown in Table 1.
[0204] <Example 5>
[0205] A latex composition before aging was obtained in the same manner as in Example 4. The pH of the obtained latex composition before aging was 11.1. Then, the obtained latex composition before aging was aged for 48 hours in the same manner as in Example 1 except that the temperature of the thermostatic water bath was adjusted to 25°C. In addition, in Example 5, no pH adjuster (potassium hydroxide aqueous solution) was added to the latex composition 12 hours after the start of aging. In addition, the pH of the latex composition 12 hours after the start of aging was 10.3, and the pH of the latex composition after aging was 10.1. Then, using the latex composition after aging for 48 hours, an immersion molded body (rubber glove) was manufactured in the same manner as in Example 1, and was evaluated in the same manner. The results are shown in Table 1.
[0206] <Comparative Example 1>
[0207] A latex composition before aging having a pH of 9.5 was obtained in the same manner as in Example 1 except that the amount of the pH adjuster (potassium hydroxide aqueous solution) added relative to the latex composition before aging was changed. Then, the obtained latex composition before aging was aged for 48 hours in the same manner as in Example 1. In addition, in Comparative Example 1, no pH adjuster (potassium hydroxide aqueous solution) was added to the latex composition 12 hours after the start of aging. In addition, the pH of the latex composition 12 hours after the start of aging was 8.5, and the pH of the latex composition after aging was 8.2. Then, using the latex composition after aging for 48 hours, a dip molded body (rubber glove) was manufactured in the same manner as in Example 1, and was evaluated in the same manner. The results are shown in Table 1. In addition, the appearance of the dip molded body (rubber glove) obtained in Comparative Example 1 can be visually confirmed to have multiple coagulants attached.
[0208] <Comparative Example 2>
[0209] A latex composition before aging having a pH of 9.5 was obtained in the same manner as in Example 1 except that sodium salt of β-naphthalenesulfonic acid formaldehyde condensate (NASF) was not added to the latex composition before aging and the amount of the pH adjuster (potassium hydroxide aqueous solution) added relative to the latex composition before aging was changed. Then, the obtained latex composition before aging was aged for 48 hours in the same manner as in Example 1. In addition, in Comparative Example 2, the pH adjuster (potassium hydroxide aqueous solution) was not added to the latex composition after 12 hours from the start of aging. In addition, the pH of the latex composition after 12 hours from the start of aging was 8.3, and the pH of the latex composition after aging was 8.1. In addition, in the latex composition obtained in Comparative Example 1, the generation of coagulation was significant (amount of coagulation: 52.5% by weight), and it was impossible to produce an impregnated molded body. The results are shown in Table 1.
[0210] [Table 1]
[0211]
[0212] As shown in Table 1, a sulfur-based vulcanizing agent and a xanthogenic acid compound are added to the prepared conjugated diene polymer latex to obtain a latex composition before aging, and then the latex composition before aging is aged so that the pH of the latex composition after 12 hours from the start of aging is 9 or more. The latex composition obtained by such a production method has excellent stability and can suppress the generation of coagulation. Furthermore, when it is made into a dip-molded body, the obtained dip-molded body has excellent tensile strength, tensile elongation, and tear strength (Examples 1 to 5). In addition, since the obtained latex composition does not contain a vulcanization accelerator that causes delayed hypersensitivity (type IV) symptoms, it can be considered that the obtained dip-molded body can prevent the occurrence of delayed hypersensitivity (type IV) when it is made into a dip-molded body.
[0213] On the other hand, when the pH of the latex composition is less than 9 12 hours after the start of aging, the stability of the obtained latex composition is poor, a large amount of coagulants are generated, and an impregnated molded body cannot be produced (Comparison Example 2). Even if an impregnated molded body can be produced, the obtained impregnated molded body has coagulants attached to it and has poor tensile strength and tear strength (Comparison Example 1).
Claims
1. A method for producing a latex composition, comprising: A preparation step of preparing a conjugated diene polymer latex; A preparation step of adding a sulfur-based vulcanizing agent and a xanthogenic acid compound to the conjugated diene polymer latex to obtain a latex composition before aging; as well as The aging step comprises: preparing the pre-aging latex composition, and then aging the pre-aging latex composition by storing the prepared pre-aging latex composition at a temperature of 5 to 60° C. for 12 hours to 14 days. The conjugated diene polymer latex is a latex of a conjugated diene polymer having no carboxyl group. In the aging step, the pH of the latex composition is set to 9 or more 12 hours after the start of aging, and the pH of the latex composition after aging is set to 10 or more.
2. The method for producing a latex composition according to claim 1, wherein In the preparation step, the pH of the latex composition before aging is set to 11 or higher.
3. The method for producing a latex composition according to claim 1 or 2, wherein: In the aging step, a pH adjuster is added to the latex composition being aged.
4. The method for producing a latex composition according to claim 3, wherein The pH adjuster includes at least one selected from the group consisting of alkali metal hydroxides, ammonia, and organic amine compounds.
5. The method for producing a latex composition according to claim 1 or 2, wherein: The sulfur-based vulcanizing agent is used in an amount of 0.01 to 3 parts by weight based on 100 parts by weight of the conjugated diene polymer contained in the conjugated diene polymer latex.
6. The method for producing a latex composition according to claim 1 or 2, wherein: The xanthogenic acid compound is used in an amount of 0.01 to 10 parts by weight based on 100 parts by weight of the conjugated diene polymer contained in the conjugated diene polymer latex.
7. The method for producing a latex composition according to claim 1 or 2, wherein: In the preparation step, a strong acid salt-based surfactant is further added to the conjugated diene polymer latex.
8. The method for producing a latex composition according to claim 1 or 2, wherein: The conjugated diene polymer latex is a latex of synthetic polyisoprene, a latex of a styrene-isoprene-styrene block copolymer, or a latex of a natural rubber from which proteins have been removed. 9 . A method for producing a dip-molded article, comprising the step of dip-molding the latex composition obtained by the production method according to claim 1 .
Citation Information
Patent Citations
Latex for dip molding use, composition for dip molding use, and dip-molded article
WO2014129547A1
Production method for latex composition
WO2019058807A1